Analysis of the spatial and temporal heterogeneity of factors influencing CO2 emissions in China’s construction industry based on the geographically and temporally weighted regression model: Evidence from 30 provinces in China - Li, Tiantian; Gao, Haidong; Yu, Jing (Frontiers in Environmental Science, 2022)
With the rapid economic development in recent years, China has increased its investment in infrastructure construction, and the construction industry has become a significant contributor to China's carbon dioxide(CO2) emissions. Therefore, carbon emission reduction in the construction industry is crucial to achieving the goal of "carbon peaking and carbon neutrality" as soon as possible. However, few studies have investigated the impact of different factors on CO2 emissions from the construction industry in terms of spatial and temporal differences. To address this gap, this paper firstly improves the calculation method for the construction industry's life cycle assessment (LCA) of CO2 emissions. It then uses a Geographically and Temporally Weighted Regression (GTWR) model to provide insight into the Spatio-temporal heterogeneity of the impact of different factors on CO2 emissions across other regions and times. The results show that: (1) CO2 emissions from the construction industry in China increased rapidly from 576.5 million tons（Mt） in 2004 to 3230 Mt in 2012 and then gradually decreased to 1998.51 Mt in 2020; indirect CO2 emissions accounted for more than 90% of the total CO2 emissions after 2008. (2) There is a solid global positive correlation between CO2 emissions from the construction industry in China during most of the study period, and the spatial distribution of CO2 emissions shows a northeast-southwest pattern, with the centre of gravity gradually shifting from central China to the southwest; (3) Economic output and industrial agglomeration are positive factors for the increase of CO2 emissions from the construction industry, and urbanization level, production efficiency, and energy efficiency are inhibiting factors for the increase of CO2 emissions from the construction industry. But the direction of fluctuation and the degree of influence of each factor differed significantly across time and regions, and each influencing factor showed substantial spatial and temporal heterogeneity. Our findings provide a scientific basis for the Chinese government to implement a regional carbon reduction strategy for the construction industry.